Photovoltaic charging multi-station with modular architecture for Light Electric Vehicles - Guillén-Arenas, Francisco Jesus; Fernández-Ramos, José; Gago-Calderón, Alfonso (My University, 2019)
This paper deals with a modular architecture for recharging the batteries of light electric vehicles (LEVs) using a photovoltaic (PV) generator. The architecture is divided into two hierarchical levels. At the top level (master), a microcontroller tracks the maximum power point of the PV generator. This microcontroller executes a PID control algorithm whose output is the setpoint of the microcontrollers of the lower level. At the lower level (slaves) there is a microcontroller for each vehicle charging station. Each microcontroller controls the recharge current of the vehicle battery connected to the station by executing another PID control algorithm. The modular architecture allows the number of charging stations to be extended to 112. Other characteristics of the system are the automatic detection of the nominal voltage of the battery (it allows to recharge batteries of 24V, 36V or 48V, equally) and the inclusion of protection functions as battery overload or detection of not allowed batteries
Keywords: Energia fotovoltaica; Light Electric Vehicle; Photovoltaic Energy; EV charging system; Solar parking lots; Sustainable mobility